Effects of Different Extraction Solvents on the Extractive Removal and Properties of Oil Palm Empty-Fruit Bunch Cellulosic Nanofibers - Solikhin, Achmad; Hadi, Yusuf Sudo; Massijaya, Muh Yusram; Nikmatin, Siti (Makara Journal of Science, 2021)
In this study, the effect of different extraction solvents on the isolation and properties of cellulosic nanofibers (CNFs) were investigated. The unextracted and different solvent-extracted CNFs formed horn-like features and irregularly aggregated nanofibers after oven drying. Scanning electron microscopy at 10000× magnification revealed the smooth external surfaces of all extracted CNFs; this finding is attributed to the limited deposition of amorphous lignocellulosic components on the fibers. All resultant CNF solutions revealed aggregation, with a particle size distribution and zeta average of 21.39–513.00 nm and 162.26–342.13 nm, respectively. Extraction with different solvents and chemical treatment yielded CNF solutions with good transparency. Increases in crystallinity indices were generated by extractive removal and enhanced the delignification and bleaching processes. The atomic crystal size of untreated and different solvent-treated CNFs varied with the type of native cellulose. A dramatic decrease in organic (i.e., C, N, and O) and inorganic (i.e., Na, K, and Si) elements was observed following extractive removal and cellulose purification